Knowledge, attitude, and preventive behaviors related to HIV/AIDS and sexually transmitted infections among Myanmar migrants in Chiang Mai province, Thailand - Thant, Kyaw Soe; Thongprachum, Aksara; Chautrakarn, Sineenart; Chantaklang, Pannawich; Chariyalertsak, Suwat (Frontiers in Public Health, 2024)
IntroductionDespite progress in controlling HIV/AIDS and STIs, these health challenges persist, with 39.9 million people living with HIV in 2023 and more than 350 million affected by STIs annually. Thailand is a major migrant hub in Southeast Asia. This study investigated the factors influencing preventive behaviors related to HIV/AIDS and STIs among Myanmar migrants in Chiang Mai province, Thailand.MethodsA cross-sectional study was conducted in 2023 among 424 Myanmar migrants aged 18–45 years. Participants were selected through convenience sampling from a local hospital and community gathering locations in Chiang Mai province. Multiple logistic regression analysis was used to identify factors influencing preventive behaviors.ResultsThe participants’ average age was 29.92 years; 56.8% were married, and 67.5% had completed primary or lower education. The average monthly income was <10,000 THB (47.6%). Most participants had a good knowledge level of HIV (63.2%), while 80% had poor knowledge of STIs. Among the sexually active participants (n = 274), 91.2% had good preventive behavior. The multivariate analysis indicated that migrants working in non-construction or day labor roles were less likely to practice preventive behaviors (aOR = 0.210, 95% CI: 0.046–0.972, p = 0.046). Additionally, migrants who had lived in Chiang Mai for more than 10 years were less likely to engage in preventive behaviors (aOR = 0.067, 95% CI: 0.010–0.465, p = 0.006). There was a statistically significant association between preventive behaviors and a positive attitude, with an aOR of 4.575 (95% CI: 1.226–17.073, p = 0.024).ConclusionLow STI knowledge and negative attitudes toward condom use were found in this study. Culturally relevant and sensitive interventions and effective sexual health education are needed.